Minding the Bathwater: Fertility and Reproductive Toxicity in the Age of Immuno-Oncology. Issue 12 (29th December 2022) - Kim, Anne E.; Nelson, Ariel; Stimpert, Kyle; Flyckt, Rebecca L.; Thirumavalavan, Nannan; Baker, Karen C.; Weinmann, Sophia C.; ,; Hoimes, Christopher J.
Abstract : Immune checkpoint inhibition has resulted in significant efficacy across many cancer types, including melanoma. Melanoma is the second most common cancer among those of reproductive age, yet the reproductive toxicities of adjuvant and first-line immunotherapy are largely unknown.The normal innate and adaptive immune systems play a vital role in reproductive organ homeostasis of men and women and are essential for implantation, fertility, and a successful pregnancy. The programmed cell death-1 receptor/programmed cell death receptor ligand-1 (PD-1/PD-L1) pathway is essential in several aspects of fertility and pregnancy. Recent studies have largely focused on the role of the PD-1/PD-L1 pathway in fetomaternal tolerance, highlighting the importance of intact immune regulation in promoting a successful pregnancy.In this review, we describe a case of a reproductive-aged female with stage IIIC melanoma who sought guidance on family planning after pembrolizumab therapy. We discuss the known fertility-related toxicities of immune checkpoint inhibitors, the potential targets for reproductive toxicity in males and nonpregnant females, and the implications of anti–PD-1 therapy in relation to fetomaternal tolerance. Informed decision making will benefit from data and consensus.